1978
DOI: 10.1128/jvi.27.2.388-398.1978
|View full text |Cite
|
Sign up to set email alerts
|

DNA of Epstein-Barr virus. III. Identification of restriction enzyme fragments that contain DNA sequences which differ among strains of Epstein-Barr virus

Abstract: Previous kinetic and absorption hybridization experiments had demonstrated that the DNA of the B95-8 strain of Epstein-Barr virus was missing approximately 10% of the DNA sequences present in the DNA of the HR-1 strain (experiments reported here, the restriction enzyme fragments of Epstein-Barr virus DNA which contain sequences which differ among the HR-1, B95-8, and W91 strains have been identified. The DNA of the HR-1, B95-8, and W91 strains each differed in complexity. The sequences previously shown to be m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
43
0

Year Published

1979
1979
1994
1994

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 28 publications
3
43
0
Order By: Relevance
“…We have shown that the restriction pattern for the B95-8 cell-associated DNA and virion DNA are the same and are consistent with the pattern for B95-8 DNA as described in other studies (Raab-Traub et al, 1978). We have also attempted to rule out the possibility that the Raji cells in our laboratory are in some way more able to allow additional gene expression of the EBV genome, since we obtained similar results with Raji cells obtained from other laboratories.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We have shown that the restriction pattern for the B95-8 cell-associated DNA and virion DNA are the same and are consistent with the pattern for B95-8 DNA as described in other studies (Raab-Traub et al, 1978). We have also attempted to rule out the possibility that the Raji cells in our laboratory are in some way more able to allow additional gene expression of the EBV genome, since we obtained similar results with Raji cells obtained from other laboratories.…”
Section: Discussionsupporting
confidence: 86%
“…The original report on B95-8 EBV (Miller et al, 1974) demonstrated that the virus was a transforming non-lytic strain of EBV; in that report unconcentrated cell supernates were used. Subsequent reports (e.g., Delius and Bornkamm, 1978;Fresen et al, 1978;Raab-Traub et al, 1978;Steinitz et al, 1978;Perlmann et al, 1982;Sairenji et al, 1982;Skare et al, 1985) make reference to this biological property of B95-8. Until recently (Takimoto et al, 1985;Sat0 et al, 1986) no EBV isolate other than HR-1 was shown to be able to lytically superinfect Raji cells.…”
mentioning
confidence: 99%
“…A variable number of tandem direct repeats of a 3,000-bp sequence, IR, separates the largely unique DNA into a segment of 14 x 103 bp, US, and a segment of 135 x 103 bp, UL (6,7,14,15,20). The DNA of the B95-8 isolate differs from most EBV DNAs in a deletion from UL of 15 x 103 bp (5,7,21,40,41). Despite this deletion, the B95-8 virus, like other EBV isolates, can infect and growth transform normal B lymphocytes and replicate in some of the transformed cell lines (33,34).…”
mentioning
confidence: 99%
“…However, the latent protein LYDMA appears not to be expressed in all BL cell lines; several EBV-positive BL lines are not susceptible to HLAmatched LYDMA-specific killing (42). Another of the latent viral functions, EBNA-2, is apparently essential for transformation in that P3HR-1, a nontransforming subclone of the transforming BL Jijoye strain, is deleted for the sequences which encode EBNA-2 (25,40,41). Superinfection of the Raji cell line with HR-1 virus generates transformationcompetent recombinants which have regained the EBNA2 sequences (44).…”
Section: Discussionmentioning
confidence: 99%